Networking and data sharing reduces hospitalization cost of heart failure: the experience of GISC study. Issue 1 (29th September 2014) - Pisanò, Franco; Lorenzoni, Giulia; Sabato, Stefano S.; Soriani, Nicola; Narraci, Ottavio; Accogli, Michele; Rosato, Carlo; de Paolis, Paola; Folino, Franco; Buja, Gianfranco; Tona, Francesco; Baldi, Ileana; et al.
Abstract Rationale, aims and objectives Heart failure (HF) is a concerning public health burden in Western society because, despite the improvement of medical treatments, it is still associated with adverse outcomes (high morbidity and mortality), resulting in one of the most expensive chronic disease in Western countries. Hospital admission particularly is the most expensive cost driver among the several resources involved in the management of HF. The aim of our study was to investigate the cost of hospitalization before and after the enrolment to a new strategy (GISC) in the management of patients with HF. Methods We enrolled a cohort of 90 patients. Patients were eligible to the study if they were hospitalized with a new diagnosis of HF or a diagnosis of decompensated HF. The enrolment to the study corresponded to the enrolment to the GISC intervention. We calculated the cost for every hospital admission at 6 and 12 months before and after the enrolment using the tariff paid for the diagnosis‐related group. Results Comparing per‐patient cumulative cost before and after the enrolment, we showed that patient's hospitalization was less expensive after the enrolment to the GISC intervention. The strategy resulted in an average cumulative estimated saving of €439 322.00 (95% CI €413 890.70; €464 753.40) at 6 months and of €832 276.80 (95% CI €786 863.70; €877 690.00) at 12 months after the enrolment. Conclusions We found out that the intervention was a cost‐saving strategy for follow‐up of the patients suffering from HF at 6 and 12 months after the enrolment compared with hospitalizations' cost before the recruitment.